A method for preparing austenitic aged steel based on injection molding
By using modified raw materials such as sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder and boron-phosphorus-chromium composite powder, etc., combined with injection molding technology, austenite aging steel was prepared, which solved the problem of poor density and mechanical properties. , achieves higher density and mechanical properties, suitable for a wider range of applications.
Patent Information
- Application Number
- CN202411768934.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The density of austenite aging steel is not high, and its mechanical properties such as tensile strength, yield strength and elongation are poor, and its hardness is low, which limits its use scenarios.
Use modified raw materials such as sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder and boron-phosphorus-chromium composite powder, combined with components such as silicon powder, manganese powder and iron powder to prepare austenite aging steel through injection molding to improve its Density and mechanical properties.
While increasing the density of austenite aging steel material, it significantly increases its mechanical properties and hardness, improves tensile strength, yield strength and elongation, and is suitable for a wider range of application scenarios.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel materials, and in particular relates to a method for preparing austenitic aging steel based on injection molding. Background Art
[0002] Austenitic aged steel refers to a type of alloy steel that is improved in strength and hardness by aging treatment (i.e., keeping it at a certain temperature for a period of time) after solution treatment; this type of steel has good plasticity and toughness in the solid solution state, and after aging treatment, its mechanical properties are significantly improved through precipitation strengthening mechanism. Austenitic aged steel is an alloy steel with high strength and toughness and good weldability. Due to its excellent mechanical properties and good processing properties, it is widely used in aerospace, automotive industry, chemical equipment, energy and other fields. Metal injection molding is a new type of powder metallurgy technology formed by introducing modern plastic injection molding technology into the field of powder metallurgy. Generally, metals or alloys that can be made into powder can be processed using metal injection molding technology. It is widely used in the production of small, three-dimensional complex shapes and products with special performance requirements.
[0003] A Chinese patent (patent number CN108907212B) discloses a method for preparing martensitic aging steel based on injection molding. The raw material powder is prefabricated into atomized alloy powder and carbonyl alloy powder. The important element Co is located in the atomized alloy powder, and Co is wrapped by other elements. During nitric acid catalytic degreasing, nitric acid corrosion of Co can be avoided, and the effect of the catalyst on Co during catalytic degreasing can be reduced. This can effectively solve the side effects of nitric acid catalytic degreasing in the prior art, and the performance of the final product is better. However, austenitic aging steel in current technology still has problems such as low density, poor mechanical properties such as tensile strength, yield strength and elongation, and low hardness, which limit its use scenarios.
[0004] Therefore, how to optimize the raw material components of austenitic aging steel to increase the density of austenitic aging steel while increasing its mechanical properties and hardness has become a key area that needs to be tackled. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing austenitic aging steel based on injection molding, aiming to solve the problems of low density, poor mechanical properties such as tensile strength, yield strength and elongation, and low hardness of the existing austenitic aging steel.
[0006] The present invention uses modified raw materials such as sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder and boron-phosphorus-chromium composite powder, and combines them with components such as silicon powder, manganese powder and iron powder to obtain austenitic aging steel through injection molding, thereby increasing the density of the austenitic aging steel material while increasing its mechanical properties and hardness.
[0007] The technical solution of the present invention is as follows:
[0008] The present invention provides a method for preparing austenitic aged steel based on injection molding, comprising the following steps:
[0009] Step S1: mixing components of molybdenum powder, nickel powder, chromium powder, silicon powder, manganese powder and iron powder and atomizing them to obtain an atomized alloy powder with a particle size D50 of 6.5-8.5 μm;
[0010] Step S2: mixing the atomized alloy powder and polyoxymethylene and kneading them, and crushing them after kneading to obtain granular feed;
[0011] Step S3: using an injection molding machine to injection mold the granular feed to obtain a rough blank;
[0012] Step S4: subjecting the rough blank to nitric acid catalytic degreasing treatment to obtain a degreased blank;
[0013] Step S5: sintering the degreased blank to obtain a sintered blank;
[0014] Step S6: heat treating the sintered blank to obtain austenitic aged steel;
[0015] The components include, by weight: 2-3 parts of molybdenum powder, 10-14 parts of nickel powder, 16-18 parts of chromium powder, 0.8-1 parts of silicon powder, 1.5-2 parts of manganese powder and 61.9-69.6 parts of iron powder; the chromium powder is a boron-phosphorus-chromium composite powder; the preparation method of the boron-phosphorus-chromium composite powder includes: by weight, adding 2-4 parts of ammonium pentaborate, 1-2 parts of boric acid, 8-10 parts of phosphoric acid and 0.5-0.8 parts of hexadecyltrimethylammonium bromide to 20-25 parts of deionized water The mixture was stirred for 1-2 hours, placed in an argon atmosphere, and reacted at 180-185°C for 10-12 hours. After the reaction was completed, it was cooled to room temperature, 1-2 parts of hydrazine hydrate were added and stirred for 1-2 hours, and then centrifuged to obtain a supernatant, which was freeze-dried to obtain boron-doped phosphorus quantum dots. 48-50 parts of chromium powder and 0.12-0.14 parts of boron-doped phosphorus quantum dots were mixed evenly, placed in a hydrogen atmosphere, and treated at 950-980°C for 2-4 hours. After cooling, a boron-phosphorus-chromium composite powder was obtained.
[0016] Phosphorus quantum dots in boron phosphorus-chromium composite powder can promote the precipitation of fine, dispersed second phase particles in the matrix material. The fine second phase particles can effectively prevent the slip of dislocations, thereby improving the hardness of austenitic aging steel.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0018] As a preferred technical solution of the present invention, the molybdenum powder in step S1 is a sulfur-carbon-molybdenum composite powder; the preparation method of the sulfur-carbon-molybdenum composite powder comprises: adding 6 to 8 parts of L-cystine hydrochloride and 3 to 4 parts of m-phenylenediamine to 15 to 20 parts of deionized water, hydrothermally reacting at 160 to 180° C. for 8 to 10 hours, centrifuging after the reaction is completed, and collecting the supernatant; adding 10 to 12 parts of the supernatant and 2 to 4 parts of polyacrylic acid to 15 to 20 parts of deionized water, stirring at 45 to 50° C. for 8 to 10 hours, and freeze-drying to obtain sulfur-modified carbon quantum dots; adding 20 to 25 parts of ammonium heptamolybdate to 100 The mixture was fully dissolved in 100-120 parts of deionized water, and then 0.1-0.2 parts of the sulfur-modified carbon quantum dots were added and mixed evenly, and then 0.01-0.03 parts of citric acid monohydrate and 0.02-0.04 parts of polyethylene glycol were added and stirred for 1-2 hours to obtain a mixed solution, and the pH of the mixed solution was adjusted to 3-4 with formic acid, and stirred at 60-80° C. for 32-35 hours to obtain a sulfur-carbon-molybdenum sol; the sulfur-carbon-molybdenum sol was kept warm at 170-190° C. under vacuum conditions for 8-10 hours to obtain a sulfur-carbon-molybdenum sol gel; the gel was ground into powder in a grinding dish, sieved, and then subjected to hydrogen reduction treatment to obtain a sulfur-carbon-molybdenum composite powder.
[0019] Preferably, the hydrogen reduction treatment comprises: using flowing hydrogen with a purity of 99.99% as a reducing carrier gas, with a hydrogen flow rate of 460-480 mL / min, reducing at 840-850° C. for 1-2 hours, and then cooling with the furnace to obtain a sulfur-carbon-molybdenum composite powder.
[0020] The sulfur-carbon-molybdenum composite powder is prepared by mixing ammonium heptamolybdate solution and carbon quantum dots to prepare a uniform sol, and then preparing the composite powder through gelation and heat treatment; in the sol-gel process, the carbon quantum dots are grown in situ in the molybdenum metal matrix through chemical reaction, so that the carbon quantum dots are evenly dispersed in the molybdenum metal matrix and agglomeration is reduced. At the same time, the sulfur-modified carbon quantum dots have more active functional groups, which are conducive to reacting with other molecules or materials and improving the density of the material. In addition, the chemical bonding between the carbon quantum dots and the molybdenum metal matrix can enhance the interface bonding force and improve the overall density of the material.
[0021] As a preferred technical solution of the present invention, the nickel powder in step S1 is a nitrogen-nickel composite powder; the preparation method of the nitrogen-nickel composite powder comprises: adding 2 to 4 parts of 2-azidoimidazole to 12 to 16 parts of tetrahydrofuran by weight and fully dissolving them, then adding 3 to 4 parts of polyethyleneimine, and reacting them at 60 to 65°C for 20 to 24 hours; after the reaction is completed, adding 1 to 2 parts of deionized water, using a rotary evaporator to spin dry the tetrahydrofuran, and then extracting it with ethyl acetate, dialyzing the aqueous solution for 8 to 10 hours, and filtering it with a membrane. Filtering, freeze-drying the filtrate to obtain nitrogen quantum dots; adding 5 to 8 parts of silane coupling agent KH550 to 100 to 120 parts of anhydrous ethanol and stirring for 10 to 20 minutes, then adding 50 to 60 parts of nickel powder, stirring at 50 to 60° C. for 30 to 40 minutes, filtering, washing, and obtaining modified nickel powder; adding 20 to 28 parts of the modified nickel powder and 0.1 to 0.2 parts of nitrogen quantum dots to 100 to 120 parts of deionized water, performing plasma spheroidization treatment, and drying to obtain nitrogen-nickel composite powder.
[0022] Preferably, the oscillation frequency of the plasma spheroidization treatment is 4-5 MHz, the plasma anode power is 20-22 kW, the powder feeding amount is 40-45 g / min, the carrier gas is nitrogen, the gas feeding amount is 0.3-0.4 m³ / h, the side gas is argon, the gas feeding amount is 4-5 m³ / h, and the center gas is argon, and the gas feeding amount is 1.2-1.5 m³ / h.
[0023] The nitrogen quantum dots in the nitrogen-nickel composite powder can act as nucleation centers to promote the refinement of austenite during the cooling process, thereby forming a finer grain structure. The smaller grain size reduces the space for dislocation movement and increases the mechanical properties of the material. At the same time, the nitrogen quantum dots can hinder the movement of dislocations through solid solution and produce lattice distortion based on size differences, thereby enhancing the tensile strength, yield strength and elongation of austenitic aged steel.
[0024] Preferably, the amount of polyoxymethylene added in step S2 is 8.9-9.2% of the mass of the atomized alloy powder.
[0025] Preferably, the injection molding conditions in step S3 are as follows: the nozzle temperature is 188-190°C, the temperature of the first section is 178-180°C, the temperature of the second section is 168-170°C, and the temperature of the third section is 158-160°C; the injection pressure is 95-100 Bar, the injection speed is 10-30 cm³ / s, the holding pressure is 95-100 Bar, the holding speed is 10-30 cm³ / s, and the holding time is 1-5 s.
[0026] Preferably, the nitric acid catalytic degreasing treatment in step S4 includes: using concentrated nitric acid with a concentration mass fraction of 95% for degreasing in a catalytic degreasing furnace, the amount of concentrated nitric acid used is 4-5g / min, the catalytic degreasing temperature is 90-130°C, nitrogen is used as the protective gas, and the nitrogen supply is 40-50L / min.
[0027] Preferably, the sintering treatment in step S5 includes: using argon as a protective gas, the argon supply rate is 25-30 L / min, the sintering temperature is 1380-1385° C., and the insulation time is 120-180 min.
[0028] Preferably, the heat treatment in step S6 includes: first performing a solution treatment and then performing an aging treatment; the temperature of the solution treatment is 1150~1200°C, the time of the solution treatment is 1~2h, and water cooling is performed after the solution treatment is completed; the temperature of the aging treatment is 880~950°C, the time of the aging treatment is 1~3h, and water cooling is performed after the aging treatment is completed.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The boron element in the boron-phosphorus-chromium composite powder of the present invention can form boron carbide with the carbon quantum dots in the carbon-sulfur-molybdenum composite powder. The good interface bonding between the boron carbide and the austenitic aged steel matrix is conducive to the effective transfer of loads and avoid stress concentration, thereby improving the comprehensive mechanical properties of the material; at the same time, the boron element combines with the nitrogen quantum dots in the nitrogen-nickel composite powder to form boron nitride. The uniform distribution of boron nitride particles in the austenitic aged steel matrix can form a dispersion strengthening effect, effectively hinder the movement of dislocations, and improve the overall hardness of the material.
[0031] (2) The present invention prepares a uniform sol by mixing an ammonium heptamolybdate solution and carbon quantum dots, and then prepares a composite powder by gelation and heat treatment. In the sol-gel process, the carbon quantum dots are grown in situ in a molybdenum metal matrix through a chemical reaction, thereby achieving uniform dispersion of the carbon quantum dots in the molybdenum metal matrix and reducing agglomeration. At the same time, the sulfur-modified carbon quantum dots have more active functional groups, which are conducive to reacting with other molecules or materials, thereby improving the density of the material. In addition, the chemical bonding between the carbon quantum dots and the molybdenum metal matrix can enhance the interface bonding force and improve the overall density of the material.
[0032] (3) The nitrogen quantum dots of the nitrogen-nickel composite powder in the present invention can act as nucleation centers to promote the refinement of austenite during the cooling process, thereby forming a finer grain structure. The smaller grain size reduces the space for dislocation movement and increases the mechanical properties of the material. At the same time, the nitrogen quantum dots can hinder the movement of dislocations through solid solution and produce lattice distortion based on size differences, thereby enhancing the tensile strength, yield strength and elongation of the austenitic aged steel.
[0033] (4) The phosphorus quantum dots of the boron phosphorus-chromium composite powder of the present invention can promote the precipitation of fine, dispersed second phase particles in the matrix material. The fine second phase particles can effectively prevent the slip of dislocations, thereby improving the hardness of austenitic aged steel. DETAILED DESCRIPTION
[0034] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0035] The sources of some components in the embodiments and comparative examples are as follows:
[0036] Molybdenum powder, item number 0082, was purchased from Tianjin Zhuxin Metal Materials Co., Ltd.;
[0037] Nickel powder, item number W5, was purchased from Huizhou Tenghui Technology Co., Ltd.;
[0038] Chromium powder, product number C105821, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0039] Silica powder, CAS No. 7440-21-3, was purchased from Sichuan Juchun Materials Technology Co., Ltd.;
[0040] Manganese powder, product number M105838, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0041] Iron powder, product number DK-Fe-001, was purchased from Beijing Dekedaojin Technology Co., Ltd.;
[0042] Polyoxymethylene, CAS No. 9002-81-7, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0043] L-Cystine hydrochloride, CAS No. 34760-60-6, purchased from Shanghai Huayuan Century Trading Co., Ltd.;
[0044] m-phenylenediamine, CAS No. 108-45-2, purchased from Jinan Century Tongda Chemical Co., Ltd.;
[0045] Polyacrylic acid, product number P131659, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0046] Ammonium heptamolybdate, CAS No. 12027-67-7, purchased from Anqing Yuetong Molybdenum Industry Co., Ltd.;
[0047] Citric acid monohydrate, CAS No. 5949-29-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0048] Polyethylene glycol, product number S30184, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0049] Formic acid, CAS No. 64-18-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0050] 2-Azidimidazole, CAS No. 56751-68-9, purchased from Tianjin Yankai Technology Co., Ltd.;
[0051] Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0052] Polyethyleneimine, product number E107079, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0053] Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0054] Silane coupling agent KH550, product number S15028, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0055] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0056] Ammonium pentaborate, CAS No. 12007-89-5, purchased from Merck Chemical Co., Ltd.;
[0057] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0058] Phosphoric acid, CAS No. 7664-38-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0059] Hexadecyltrimethylammonium bromide, CAS number 57-09-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0060] Hydrazine hydrate, CAS No. 7803-57-8, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0061] Preparation of boron-phosphorus-chromium composite powder: In parts by weight, 4 parts of ammonium pentaborate, 2 parts of boric acid, 10 parts of phosphoric acid and 0.8 parts of hexadecyltrimethylammonium bromide are added to 25 parts of deionized water and stirred for 2 hours, placed in an argon atmosphere, and reacted at 185°C for 10 hours. After the reaction is completed, it is cooled to room temperature, 2 parts of hydrazine hydrate are added and stirred for 2 hours, and then centrifuged to obtain a supernatant, and the supernatant is freeze-dried to obtain boron-doped phosphorus quantum dots; 48 parts of chromium powder and 0.12 parts of boron-doped phosphorus quantum dots are mixed evenly, placed in a hydrogen atmosphere, treated at 980°C for 2 hours, and cooled to obtain a boron-phosphorus-chromium composite powder.
[0062] Preparation of sulfur-carbon-molybdenum composite powder: by weight, 8 parts of L-cystine hydrochloride and 4 parts of m-phenylenediamine were added to 20 parts of deionized water, and the mixture was hydrothermally reacted at 180°C for 8 hours. After the reaction was completed, the mixture was centrifuged and the supernatant was collected; 12 parts of the supernatant and 4 parts of polyacrylic acid were added to 20 parts of deionized water, stirred at 50°C for 8 hours, and freeze-dried to obtain sulfur-modified carbon quantum dots; 25 parts of ammonium heptamolybdate were added to 120 parts of deionized water and fully dissolved, and then 0.2 parts of the sulfur-modified carbon quantum dots were added and mixed evenly, and then 0.03 parts of monohydrated lemon were added. Acid and 0.04 parts of polyethylene glycol, stirring for 2 hours to obtain a mixed solution, adjusting the pH of the mixed solution to 4 with formic acid, stirring at 80°C for 35 hours to obtain a sulfur-carbon-molybdenum sol; keeping the sulfur-carbon-molybdenum sol at 190°C under vacuum for 8 hours to obtain a sulfur-carbon-molybdenum sol gel; grinding the gel into powder in a grinding dish, sieving it, and then performing hydrogen reduction treatment, using flowing hydrogen with a purity of 99.99% as a reducing carrier gas, with a hydrogen flow rate of 480 mL / min, reducing it at 850°C for 1 hour, and cooling it with the furnace to obtain a sulfur-carbon-molybdenum composite powder.
[0063] Preparation of the nitrogen-nickel composite powder: by weight, 4 parts of 2-azidoimidazole are fully dissolved in 16 parts of tetrahydrofuran, and then 4 parts of polyethyleneimine are added, and the reaction is carried out at 65° C. for 20 hours; after the reaction is completed, 2 parts of deionized water are added, and the tetrahydrofuran is dried by rotary evaporator, and then extracted with ethyl acetate, and the aqueous phase solution is dialyzed for 10 hours, filtered with a filter membrane, and the filtrate is freeze-dried to obtain nitrogen quantum dots; 8 parts of silane coupling agent KH550 are added to 120 parts of anhydrous ethanol and stirred for 20 minutes, and then 60 parts of nickel powder are added, and the mixture is stirred for 20 minutes. The mixture was stirred at 60°C for 30 min, filtered, and washed to obtain modified nickel powder; 28 parts of the modified nickel powder and 0.2 parts of nitrogen quantum dots were added to 120 parts of deionized water for plasma spheroidization treatment, the oscillation frequency of the ion spheroidization treatment was 5 MHz, the plasma anode power was 22 KW, the powder feeding amount was 45 g / min, the carrier gas was nitrogen, the gas feeding amount was 0.4 m³ / h, the side gas was argon, the gas feeding amount was 5 m³ / h, the center gas was argon, the gas feeding amount was 1.5 m³ / h, and the nitrogen-nickel composite powder was obtained by drying.
[0064] Embodiment 1:
[0065] This embodiment provides a method for preparing austenitic aged steel based on injection molding, comprising the following steps:
[0066] Step S1: mixing sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder, boron-phosphorus-chromium composite powder, silicon powder, manganese powder and iron powder and atomizing them to obtain an atomized alloy powder with a particle size D50 of 8.5 μm;
[0067] Step S2: mixing the atomized alloy powder and polyoxymethylene and kneading them, and crushing them after kneading to obtain granular feed; the amount of polyoxymethylene added is 9.2% of the mass of the atomized alloy powder;
[0068] Step S3: using an injection molding machine to injection mold the granular feed to obtain a rough blank; the injection molding conditions include a nozzle temperature of 190°C, a first stage temperature of 180°C, a second stage temperature of 170°C, and a third stage temperature of 160°C; an injection pressure of 100 Bar, an injection speed of 30 cm³ / s, a holding pressure of 100 Bar, a holding speed of 30 cm³ / s, and a holding time of 1 s;
[0069] Step S4: subjecting the rough blank to nitric acid catalytic degreasing treatment to obtain a degreased blank; the nitric acid catalytic degreasing treatment comprises using concentrated nitric acid with a concentration mass fraction of 95% to degrease in a catalytic degreasing furnace, the amount of concentrated nitric acid used is 5 g / min, the catalytic degreasing temperature is 130° C., nitrogen is used as a protective gas, and the nitrogen supply rate is 50 L / min;
[0070] Step S5: sintering the debinded blank to obtain a sintered blank; the sintering process includes using argon as a protective gas, the argon supply rate is 30L / min, the sintering temperature is 1385°C, and the holding time is 180min;
[0071] Step S6: heat treating the sintered blank to obtain austenitic aged steel; the heat treatment includes first performing a solution treatment and then performing an aging treatment; the temperature of the solution treatment is 1200°C, the time of the solution treatment is 1 hour, and water cooling is performed after the solution treatment is completed; the temperature of the aging treatment is 950°C, the time of the aging treatment is 1 hour, and water cooling is performed after the aging treatment is completed;
[0072] The components include, by weight: 3 parts of sulfur-carbon-molybdenum composite powder, 14 parts of nitrogen-nickel composite powder, 18 parts of boron-phosphorus-chromium composite powder, 1 part of silicon powder, 2 parts of manganese powder and 61.9 parts of iron powder.
[0073] Embodiment 2:
[0074] This embodiment provides a method for preparing austenitic aged steel based on injection molding, comprising the following steps:
[0075] Step S1: mixing sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder, boron-phosphorus-chromium composite powder, silicon powder, manganese powder and iron powder and atomizing them to obtain an atomized alloy powder with a particle size D50 of 6.5 μm;
[0076] Step S2: mixing the atomized alloy powder and polyoxymethylene and kneading them, and crushing them after kneading to obtain granular feed; the amount of polyoxymethylene added is 8.9% of the mass of the atomized alloy powder;
[0077] Step S3: using an injection molding machine to injection mold the granular feed to obtain a rough blank; the injection molding conditions include a nozzle temperature of 188°C, a first stage temperature of 178°C, a second stage temperature of 168°C, and a third stage temperature of 158°C; an injection pressure of 95 Bar, an injection speed of 10 cm³ / s, a holding pressure of 95 Bar, a holding speed of 10 cm³ / s, and a holding time of 5 s;
[0078] Step S4: subjecting the rough blank to nitric acid catalytic degreasing treatment to obtain a degreased blank; the nitric acid catalytic degreasing treatment comprises using concentrated nitric acid with a concentration mass fraction of 95% to degrease in a catalytic degreasing furnace, the amount of concentrated nitric acid used is 4 g / min, the catalytic degreasing temperature is 90° C., nitrogen is used as a protective gas, and the nitrogen supply rate is 40 L / min;
[0079] Step S5: sintering the debinded blank to obtain a sintered blank; the sintering process includes using argon as a protective gas, the argon supply rate is 25L / min, the sintering temperature is 1380°C, and the holding time is 180min;
[0080] Step S6: heat treating the sintered blank to obtain austenitic aged steel; the heat treatment includes first performing a solution treatment and then performing an aging treatment; the temperature of the solution treatment is 1150°C, the time of the solution treatment is 2 hours, and water cooling is performed after the solution treatment is completed; the temperature of the aging treatment is 880°C, the time of the aging treatment is 3 hours, and water cooling is performed after the aging treatment is completed;
[0081] The components include, by weight: 2 parts of sulfur-carbon-molybdenum composite powder, 10 parts of nitrogen-nickel composite powder, 16 parts of boron-phosphorus-chromium composite powder, 0.8 parts of silicon powder, 1.5 parts of manganese powder and 69.6 parts of iron powder.
[0082] Embodiment 3:
[0083] This embodiment provides a method for preparing austenitic aged steel based on injection molding, comprising the following steps:
[0084] Step S1: mixing sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder, boron-phosphorus-chromium composite powder, silicon powder, manganese powder and iron powder and atomizing them to obtain an atomized alloy powder with a particle size D50 of 7.5 μm;
[0085] Step S2: mixing the atomized alloy powder and polyoxymethylene and kneading them, and crushing them after kneading to obtain granular feed; the amount of polyoxymethylene added is 9.1% of the mass of the atomized alloy powder;
[0086] Step S3: using an injection molding machine to injection mold the granular feed to obtain a rough blank; the injection molding conditions include a nozzle temperature of 189°C, a first stage temperature of 179°C, a second stage temperature of 169°C, and a third stage temperature of 159°C; an injection pressure of 98 Bar, an injection speed of 25 cm³ / s, a holding pressure of 98 Bar, a holding speed of 25 cm³ / s, and a holding time of 3s;
[0087] Step S4: subjecting the rough blank to nitric acid catalytic degreasing treatment to obtain a degreased blank; the nitric acid catalytic degreasing treatment comprises using concentrated nitric acid with a concentration mass fraction of 95% to degrease in a catalytic degreasing furnace, the amount of concentrated nitric acid used is 4 g / min, the catalytic degreasing temperature is 110° C., nitrogen is used as a protective gas, and the nitrogen supply rate is 48 L / min;
[0088] Step S5: sintering the degreased blank to obtain a sintered blank; the sintering process includes using argon as a protective gas, the argon supply rate is 26L / min, the sintering temperature is 1382°C, and the holding time is 150min;
[0089] Step S6: heat treating the sintered blank to obtain austenitic aged steel; the heat treatment includes first performing a solution treatment and then performing an aging treatment; the temperature of the solution treatment is 1180°C, the time of the solution treatment is 2 hours, and water cooling is performed after the solution treatment is completed; the temperature of the aging treatment is 920°C, the time of the aging treatment is 2 hours, and water cooling is performed after the aging treatment is completed;
[0090] The components include, by weight: 2.5 parts of sulfur-carbon-molybdenum composite powder, 12 parts of nitrogen-nickel composite powder, 17 parts of boron-phosphorus-chromium composite powder, 0.9 parts of silicon powder, 1.8 parts of manganese powder and 65.7 parts of iron powder.
[0091] Comparative Example 1:
[0092] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which differs from Example 1 in that commercially available molybdenum powder is used instead of sulfur-carbon-molybdenum composite powder, commercially available nickel powder is used instead of nitrogen-nickel composite powder, and commercially available chromium powder is used instead of boron-phosphorus-chromium composite powder.
[0093] Comparative Example 2:
[0094] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which is different from Example 1 in that commercially available nickel powder is used instead of nitrogen-nickel composite powder, and commercially available chromium powder is used instead of boron phosphorus-chromium composite powder.
[0095] Comparative Example 3:
[0096] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which differs from Example 1 in that commercially available molybdenum powder is used instead of sulfur-carbon-molybdenum composite powder, and commercially available chromium powder is used instead of boron-phosphorus-chromium composite powder.
[0097] Comparative Example 4:
[0098] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which is different from Example 1 in that commercially available molybdenum powder is used instead of sulfur-carbon-molybdenum composite powder, and commercially available nickel powder is used instead of nitrogen-nickel composite powder.
[0099] Comparative Example 5:
[0100] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which is different from Example 1 in that commercially available molybdenum powder is used instead of sulfur-carbon-molybdenum composite powder.
[0101] Comparative Example 6:
[0102] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which is different from Example 1 in that commercially available nickel powder is used instead of nitrogen-nickel composite powder.
[0103] Comparative Example 7:
[0104] This comparative example provides a method for preparing austenitic aged steel based on injection molding, which is different from Example 1 in that commercially available chromium powder is used instead of boron phosphorus-chromium composite powder.
[0105] The performance of the austenitic aging steel provided in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0106] Density test: refer to the requirements of ISO 3369:2006 Density determination method of dense sintered metal materials and cemented carbides for testing.
[0107] Mechanical properties test: Test in accordance with the requirements of GB / T 228.1-2021 Tensile test of metallic materials Part 1: Room temperature test method.
[0108] Hardness test: Test according to the requirements of GB / T 230.1-2018 Rockwell hardness test for metallic materials Part 1: Test method.
[0109] The above performance test data is shown in Table 1.
[0110]
[0111] From the above content, it can be seen that the present invention uses modified raw materials such as sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder and boron-phosphorus-chromium composite powder, and cooperates with components such as silicon powder, manganese powder and iron powder to obtain austenitic aged steel (Examples 1~3) by injection molding, and its density is 7.88~7.89 g / cm³, and its mechanical properties include tensile strength, yield strength and elongation, wherein the tensile strength is 511~514 MPa, the yield strength is 231~236 MPa, the elongation is 42.22~42.25%, and the hardness is 154~157 HV.
[0112] Compared with Example 1, commercially available molybdenum powder is used to replace sulfur-carbon-molybdenum composite powder, commercially available nickel powder is used to replace nitrogen-nickel composite powder, and commercially available chromium powder is used to replace boron-phosphorus-chromium composite powder, then the density of austenitic aging steel becomes smaller, the mechanical properties decrease, and the hardness decreases (Comparative Example 1); Compared with Example 1, commercially available nickel powder is used to replace nitrogen-nickel composite powder, and commercially available chromium powder is used to replace boron-phosphorus-chromium composite powder, then the mechanical properties of austenitic aging steel decrease, and the hardness decreases (Comparative Example 2); Compared with Example 1, commercially available molybdenum powder is used to replace sulfur-carbon-molybdenum composite powder, and commercially available chromium powder is used to replace boron-phosphorus-chromium composite powder, then the density of austenitic aging steel decreases, the mechanical properties decrease, and the hardness decreases (Comparative Example 3); Compared with Example 1, commercially available molybdenum powder is used to replace the sulfur-carbon-molybdenum composite powder, and commercially available nickel powder is used to replace the nitrogen-nickel composite powder, then the density of the austenitic aging steel becomes smaller, the mechanical properties decrease, and the hardness decreases (Comparative Example 4); Compared with Example 1, commercially available molybdenum powder is used to replace the sulfur-carbon-molybdenum composite powder, the density of the austenitic aging steel becomes smaller, and the mechanical properties decrease (Comparative Example 5); Compared with Example 1, commercially available nickel powder is used to replace the nitrogen-nickel composite powder, the mechanical properties of the austenitic aging steel decrease, and the hardness decreases (Comparative Example 6); Compared with Example 1, commercially available chromium powder is used to replace the boron-phosphorus-chromium composite powder, the mechanical properties of the austenitic aging steel decrease, and the hardness decreases (Comparative Example 7).
[0113] In summary, the present invention uses modified raw materials such as sulfur-carbon-molybdenum composite powder, nitrogen-nickel composite powder and boron-phosphorus-chromium composite powder, and combines components such as silicon powder, manganese powder and iron powder to obtain austenitic aging steel through injection molding, thereby increasing the density of the austenitic aging steel material while increasing its mechanical properties and hardness.
[0114] The applicant declares that the present invention uses the above embodiments to illustrate the detailed process flow of the present invention, but the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention falls within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing austenitic aged steel based on injection molding, characterized in that: The following steps are involved: Step S1: mixing components of molybdenum powder, nickel powder, chromium powder, silicon powder, manganese powder and iron powder and atomizing them to obtain an atomized alloy powder with a particle size D50 of 6.5-8.5 μm; Step S2: mixing the atomized alloy powder and polyoxymethylene and kneading them, and crushing them after kneading to obtain granular feed; Step S3: using an injection molding machine to injection mold the granular feed to obtain a rough blank; Step S4: subjecting the rough blank to nitric acid catalytic degreasing treatment to obtain a degreased blank; Step S5: sintering the degreased blank to obtain a sintered blank; Step S6: heat treating the sintered blank to obtain austenitic aged steel; The components include, by weight: 2 to 3 parts of molybdenum powder, 10 to 14 parts of nickel powder, 16 to 18 parts of chromium powder, 0.8 to 1 parts of silicon powder, 1.5 to 2 parts of manganese powder and 61.9 to 69.6 parts of iron powder; The chromium powder is a boron-phosphorus-chromium composite powder; the preparation method of the boron-phosphorus-chromium composite powder comprises: adding 2-4 parts of ammonium pentaborate, 1-2 parts of boric acid, 8-10 parts of phosphoric acid and 0.5-0.8 parts of hexadecyltrimethylammonium bromide to 20-25 parts of deionized water by weight, stirring for 1-2 hours, placing in an argon atmosphere, reacting at 180-185° C. for 10-12 hours, cooling to room temperature after the reaction, adding 1-2 parts of hydrazine hydrate and stirring for 1-2 hours, then centrifuging to obtain a supernatant, freeze-drying the supernatant to obtain boron-doped phosphorus quantum dots; uniformly mixing 48-50 parts of chromium powder and 0.12-0.14 parts of boron-doped phosphorus quantum dots, placing in a hydrogen atmosphere, treating at 950-980° C. for 2-4 hours, and cooling to obtain the boron-phosphorus-chromium composite powder.
2. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The molybdenum powder in step S1 is a sulfur-carbon-molybdenum composite powder; the preparation method of the sulfur-carbon-molybdenum composite powder comprises: adding 6 to 8 parts of L-cystine hydrochloride and 3 to 4 parts of m-phenylenediamine to 15 to 20 parts of deionized water, hydrothermally reacting at 160 to 180° C. for 8 to 10 hours, centrifuging after the reaction is completed, and collecting the supernatant; adding 10 to 12 parts of the supernatant and 2 to 4 parts of polyacrylic acid to 15 to 20 parts of deionized water, stirring at 45 to 50° C. for 8 to 10 hours, and freeze-drying to obtain sulfur-modified carbon quantum dots; adding 20 to 25 parts of ammonium heptamolybdate to 100 to 120 parts of deionized water; The mixture is fully dissolved in water, and then 0.1-0.2 parts of the sulfur-modified carbon quantum dots are added and mixed evenly, and then 0.01-0.03 parts of citric acid monohydrate and 0.02-0.04 parts of polyethylene glycol are added and stirred for 1-2 hours to obtain a mixed solution, and the pH of the mixed solution is adjusted to 3-4 with formic acid, and stirred at 60-80° C. for 32-35 hours to obtain a sulfur-carbon-molybdenum sol; the sulfur-carbon-molybdenum sol is kept warm at 170-190° C. under vacuum conditions for 8-10 hours to obtain a sulfur-carbon-molybdenum sol gel; the gel is ground into powder in a grinding dish, sieved, and then subjected to hydrogen reduction treatment to obtain a sulfur-carbon-molybdenum composite powder.
3. The method for preparing austenitic aged steel based on injection molding according to claim 2, characterized in that: The hydrogen reduction treatment comprises: using flowing hydrogen with a purity of 99.99% as a reduction carrier gas, with a hydrogen flow rate of 460-480 mL / min, reducing for 1-2 hours at 840-850° C., and cooling with the furnace to obtain a sulfur-carbon-molybdenum composite powder.
4. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The nickel powder in step S1 is a nitrogen-nickel composite powder; the preparation method of the nitrogen-nickel composite powder comprises: adding 2-4 parts of 2-azidoimidazole to 12-16 parts of tetrahydrofuran by weight to fully dissolve, then adding 3-4 parts of polyethyleneimine, and reacting at 60-65°C for 20-24 hours; after the reaction is completed, adding 1-2 parts of deionized water, using a rotary evaporator to spin dry the tetrahydrofuran, and then extracting with ethyl acetate, dialyzing the aqueous solution for 8-10 hours, filtering with a filter membrane, and freezing the filtrate. The method comprises the steps of: drying to obtain nitrogen quantum dots; adding 5 to 8 parts of a silane coupling agent KH550 to 100 to 120 parts of anhydrous ethanol, stirring for 10 to 20 minutes, then adding 50 to 60 parts of nickel powder, stirring for 30 to 40 minutes at 50 to 60° C., filtering, washing, and obtaining modified nickel powder; adding 20 to 28 parts of the modified nickel powder and 0.1 to 0.2 parts of nitrogen quantum dots to 100 to 120 parts of deionized water, performing plasma spheroidization treatment, and drying to obtain nitrogen-nickel composite powder.
5. The method for preparing austenitic aged steel based on injection molding according to claim 4, characterized in that: The oscillation frequency of the plasma spheroidization treatment is 4~5MHz, the plasma anode power is 20~22KW, the powder feeding amount is 40~45g / min, the carrier gas is nitrogen, the gas feeding amount is 0.3~0.4m³ / h, the side gas is argon, the gas feeding amount is 4~5m³ / h, and the center gas is argon, and the gas feeding amount is 1.2~1.5m³ / h.
6. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The amount of polyoxymethylene added in step S2 is 8.9-9.2% of the mass of the atomized alloy powder.
7. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The injection molding conditions in step S3 are as follows: the nozzle temperature is 188-190°C, the temperature of the first section is 178-180°C, the temperature of the second section is 168-170°C, and the temperature of the third section is 158-160°C; the injection pressure is 95-100 Bar, the injection speed is 10-30 cm³ / s, the holding pressure is 95-100 Bar, the holding speed is 10-30 cm³ / s, and the holding time is 1-5 s.
8. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The nitric acid catalytic degreasing treatment in step S4 includes: using concentrated nitric acid with a concentration mass fraction of 95% for degreasing in a catalytic degreasing furnace, the amount of concentrated nitric acid used is 4-5g / min, the catalytic degreasing temperature is 90-130°C, nitrogen is used as the protective gas, and the nitrogen supply is 40-50L / min.
9. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The sintering treatment in step S5 includes: using argon as a protective gas, the argon supply rate is 25-30 L / min, the sintering temperature is 1380-1385° C., and the insulation time is 120-180 min.
10. The method for preparing austenitic aged steel based on injection molding according to claim 1, characterized in that: The heat treatment in step S6 includes: first performing a solution treatment and then performing an aging treatment; the temperature of the solution treatment is 1150~1200°C, the time of the solution treatment is 1~2h, and water cooling is performed after the solution treatment is completed; the temperature of the aging treatment is 880~950°C, the time of the aging treatment is 1~3h, and water cooling is performed after the aging treatment is completed.
Citation Information
Patent Citations
A method for preparing martensitic aging steel based on injection molding
CN108907212B
Amorphous alloy containing feedstock for powder injection molding
CN106062234A
Method for improving strength and corrosion resistance of austenitic stainless steel powder injection molding product
CN114101674A